2013
DOI: 10.1016/j.vetpar.2012.07.030
|View full text |Cite
|
Sign up to set email alerts
|

First record of Chilodonella hexasticha (Ciliophora: Chilodonellidae) in Brazilian cultured fish: A morphological and pathological assessment

Abstract: Chilodonelids are small ciliated protozoans found worldwide and can be dangerous in culture conditions. This study presents morphometric data on the ciliate Chilodonella that is found in cultured Nile tilapia (Oreochromis niloticus), native bait fish tuvira (Gymnotus aff. inaequilabiatus) and native pacu (Piaractus mesopotamicus) and includes a histopathological assessment of the changes that occur in the pacu. For parasitic diagnosis, skin and gill samples were scraped onto slides, dried at room temperature, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(61 citation statements)
references
References 19 publications
2
58
0
1
Order By: Relevance
“…Macro and micronucleus well evidenced ( Figure 2c); the ventral surface has two longitudinal rows of ciliary kineties (Figure 2b,d) (PÁDUA et al, 2013a). Chilodonella species are free-living but some of them parasitize the skin, gills and fins of both freshwater, marine and estuary fish (PÁDUA et al, 2013a).…”
Section: Pathogenesis and Clinical Signsmentioning
confidence: 99%
See 2 more Smart Citations
“…Macro and micronucleus well evidenced ( Figure 2c); the ventral surface has two longitudinal rows of ciliary kineties (Figure 2b,d) (PÁDUA et al, 2013a). Chilodonella species are free-living but some of them parasitize the skin, gills and fins of both freshwater, marine and estuary fish (PÁDUA et al, 2013a).…”
Section: Pathogenesis and Clinical Signsmentioning
confidence: 99%
“…C. cyprini Moroff, 1902) mainly parasitizing fishes from subtropical and temperate waters. In Brazil, Pádua et al (2013a) have reported for the first time C. hexasticha causing outbreak mortality in Nile tilapia (Oreochromis niloticus), pacu (Piaractus mesopotamicus), and tuvira (Gymnotus aff. inaequilabiatus).…”
Section: Pathogenesis and Clinical Signsmentioning
confidence: 99%
See 1 more Smart Citation
“…menginfeksi insang, sedangkan menurut Padua et al (2013) parasit tersebut menginfeksi permukaan kulit, insang, dan sirip prevalensi Chilodonella sp. pada penelitian ini 4 sedangkan Poulin et al (2012) melaporkan infeksi parasit tersebut sebesar 1.…”
Section: Pendahuluanunclassified
“…bras., Brasília, v.51, n.4, p.5, p.520-526, maio 2016 DOI: 10.1590/S0100-204X2016000500012 of microorganisms that can act as pathogens. Ciliates, including Trichodina heterodentata (Martins et al, 2010;Pádua et al, 2012b;Valladão et al, 2014), Paratrichodina africana (Valladão et al, 2013), Chilodonella hexasticha (Pádua et al, 2013b), and Epistylis sp. (Fernández, 2012;Pádua et al, 2013a;Valladão et al, 2015), have recently been reported to cause important diseases in farmed fish in South America, being considered emerging pathogens in aquaculture.…”
Section: Introductionmentioning
confidence: 99%